Compressive strain induced superior HER performance of nickel in alkaline solution. Issue 45 (11th November 2022) - Xiao, Zechen; Li, Zhi; Jing, Yuhan; Li, Ting; Jiang, Dongyang; Duan, Yuxian; Ye, Qianxu; Zhou, Liexing; Chen, Anran; Cai, Jinming
Abstract : The as-prepared EG–Ni with compressive strain accelerates the occurrence of the hydrogen evolution reaction, and reduces the energy consumption. Abstract : The HER requires a highly efficient, cost-effective, and stable catalyst to adapt to the large-scale hydrogen industry. Nickel has been confirmed to be useful to drive the water splitting reaction, but the intrinsic performance remains unsatisfactory. In this work, nickel (EG–Ni) with compressive strain was prepared through a one-step electrochemical deposition strategy. It shows an outstanding enhancement for the HER, and it achieves a current density of 10 mA cm −2 at a low overpotential of 85.9 mV. A long-term durability test proves that the EG–Ni can tolerate a large current density of 100 mA cm −2, and the overpotential remains steady without dramatically increasing. Such a low overpotential and superior stability are attributed to the optimized adsorption energy on the catalyst surface, as evidenced by the downshifted position of the d-band center.